Morphological and functional changes in spectral domain optical coherence tomography and microperimetry in macular microhole variants: Spectral domain optical coherence tomography and microperimetry correlation - Gella, Laxmi (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: To evaluate the relationship between the morphology and retinal function of macular microhole (MMH) variants. MATERIALS AND METHODS: We evaluated 12 eyes of 11 patients with defects in the IS/OS junction of photoreceptor layer with SD-OCT. All patients underwent comprehensive ophthalmic examination including spectral domain optical coherence tomography (SD-OCT) and microperimetry. RESULTS: The mean logMAR visual acuity in the affected eye was 0.15 ± 0.17 (range 0.00–0.5). Mean horizontal diameter of the MMH was 163 ± 99 μm; the mean retinal sensitivity in the area corresponding to the MMH was 13.79 ± 4.6 dB. Negative correlation was found between the MMH diameter and the retinal sensitivity (r = -0.65, p = 0.02). Three morphological patterns of MMH variants were recognized on SD-OCT, which did not differ in retinal sensitivities. CONCLUSION: We described and classified the MMH variants and made an assessment on the physiological functions using microperimeter.